SPATIAL VISUALIZATION SKILS IN QUANTITY SURVEYING EDUCATION: STUDENTS’ PERCEPTION OF 3D LEARNING ENVIRONMENT - John, Iniobong Beauty; Owolabi, Oyinkansola; Adekunle, Samuel; Aigbavboa, Clinton (Journal of Surveying, Construction and Property, 2025)
Traditional teaching methodologies reliant on 2D drawings and static diagrams have proven inadequate in conveying complex spatial relationships, hindering students' ability to bridge theoretical knowledge and practical application. To address these deficiencies, this research examines undergraduate students' perceptions of 3D learning tools, emphasizing their impact on enhancing spatial awareness, engagement, and practical proficiency. Data was gathered through a structured online survey targeting Quantity Surveying (QS) students in a Nigerian university, measuring their confidence in interpreting building plans, identifying spatial relationships, and utilizing software tools for measurement. Results indicate significant variation in spatial visualization abilities across academic levels, with senior students displaying higher confidence, attributed to accumulated experience. However, challenges persist in accurately identifying spatial relationships, underscoring a need for enhanced technological integration in teaching. The study reveals a strong preference among students for 3D modeling and virtual reality (VR) tools, highlighting their potential to transform QS education. Despite the promise of 3D learning environment, barriers such as inadequate infrastructure, limited faculty expertise, and insufficient access to technology impede effective implementation. This research advocates for a paradigm shift towards immersive, technology-driven pedagogies to better align QS education with industry demands, thereby fostering competent professionals capable of meeting modern construction challenges.